2016
DOI: 10.1111/aos.13155
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk management – a 3‐year experience of team timeout in 18 081 ophthalmic patients

Abstract: Team timeout proved valuable, as it improved the patients' safety with minimum effort. Errors may occur despite several preoperative controls and can be detected by performing team timeout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…There is a Team timeout, which has proven useful in improving patient safety with minimal effort. Despite various preoperative safeguards, errors can occur and can be detected by performing a team timeout (Weingessel et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a Team timeout, which has proven useful in improving patient safety with minimal effort. Despite various preoperative safeguards, errors can occur and can be detected by performing a team timeout (Weingessel et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although SSC implementation remains inadequate in this comprehensive analysis, the surgical safety checklist implementation reduced patient mortality in surgery (Ramsay et al 2019), reduced the occurrence and problem in surgery (Barbanti-Brodano et al 2020), avoid complications and unintended errors (Harris et al 2020), despite several preoperative protections, errors can occur and can be caught by performing a team timeout. (Weingessel et al 2017) and become a simple technique that can considerably improve patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, it is noted that in ten, categorized as "Importance of the checklist", the authors emphasized the importance and need to use the list to minimize adverse events and better interaction and communication between the team that works in the Surgical Center. [7][8][9][10][11][12][13][14][15][16] Research indicates that performing a safe surgery checklist is one of the most effective tools to avoid errors and adverse events in hospitals. A study published in 2009 in The New England Journal of Medicine showed that the mortality rate and surgical complications were reduced by more than 30% in hospitals that participated in the WHO pilot program to implement the surgical checklist.…”
Section: Discussionmentioning
confidence: 99%
“…According to Neiley et al (2009) ophthalmic surgery is associated with the highest rate of complications. A study conducted on the WHO checklist for ophthalmic surgery concluded that the checklist is valuable in reducing errors and improving patient safety (Weingessel et al 2016). This indirectly highlighted the importance of keeping to the original list order in ophthalmic surgery to reduce the number of incidents.…”
Section: Discussionmentioning
confidence: 99%